The dynamic relationship between trading volume, stock return, and volatility-domestic and cross-country: South Asian markets - Miseman, M. R.; Yahya, M. H.; Mustafa, Hasri; Lee, Yok Yong (Finance, Accounting and Business Analysis, 2019)
This paper examines the contemporaneous and dynamic relationships among trading volumes, stock returns and return volatility for three emerging markets in Southeast Asia, which are Malaysia, Indonesia and Singapore. Tests on both intra-and inter-market relationships between the variables are conducted to determine whether they are interrelated within the same market and across the markets. The paper also applies GARCH technique to model the volatility of returns for the three stock markets of concern. The study finds strong evidence of asymmetry in the relationship between the stock returns and trading volume; whereby returns are significant in predicting their future dynamics, as well as, the trading volume. However, trading volume has a very limited power on the future dynamics of stock returns. The study also finds bidirectional causality between trading volume and volatility of returns in Malaysia and Singapore. In particular, Singapore market can be perceived as the focal stock exchange that has cross-market relationships with its other two neighbors.